2016
DOI: 10.1007/s10803-016-2802-9
|View full text |Cite
|
Sign up to set email alerts
|

In the Eye of the Beholder: Rapid Visual Perception of Real-Life Scenes by Young Adults with and Without ASD

Abstract: Typically developing (TD) adults are able to extract global information from natural images and to categorize them within a single glance. This study aimed at extending these findings to individuals with autism spectrum disorder (ASD) using a free description open-encoding paradigm. Participants were asked to freely describe what they saw when looking at briefly presented real-life photographs. Our results show subtle but consistent group-level differences. More specifically, individuals with ASD spontaneously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 75 publications
(74 reference statements)
0
9
0
Order By: Relevance
“…Vanmarcke and Wagemans found that higher autistic traits (within a general population) were associated with more effective processing of high spatial frequency (fine, detailed analysis) in conditions with more time. ASD was found to be associated with deficits in the rapid processing of social relations specifically from visual scenes (Vanmarcke et al, 2016a;. Future research can establish whether Type 1 and 2 processing within the context of reasoning relate to these differences in rapid visual perception and categorisation of real-life scenes as well as established differences in perceptual and cognitive assessments of global, gist, or gestalt processing (e.g.…”
Section: Discussionmentioning
confidence: 94%
“…Vanmarcke and Wagemans found that higher autistic traits (within a general population) were associated with more effective processing of high spatial frequency (fine, detailed analysis) in conditions with more time. ASD was found to be associated with deficits in the rapid processing of social relations specifically from visual scenes (Vanmarcke et al, 2016a;. Future research can establish whether Type 1 and 2 processing within the context of reasoning relate to these differences in rapid visual perception and categorisation of real-life scenes as well as established differences in perceptual and cognitive assessments of global, gist, or gestalt processing (e.g.…”
Section: Discussionmentioning
confidence: 94%
“…In contrast to their superior search ability, autistic individuals are worse in the extraction of global information from natural images [111]. They are slower in tasks where participants are asked to describe the gist of the presented scene when looking at briefly present real-life photographs [111].…”
Section: Visual Scene Analysis In Autismmentioning
confidence: 99%
“…They are slower in tasks where participants are asked to describe the gist of the presented scene when looking at briefly present real-life photographs [111]. Some researchers have pointed out that although autistic individuals have a reduced tendency to report global features of a stimulus when offered a choice of what features to report, they perform similarly to NT individuals when explicitly instructed to attend to global features [112].…”
Section: Visual Scene Analysis In Autismmentioning
confidence: 99%
“…If the task requires more detail, information is fed back to the lower areas of the visual brain for further processing. One view is that these two processes are out of balance in individuals with ASD: Fast extraction of global gist is less efficient, but attention‐driven processing of local elements is superior. This integrated framework unites WCC and EPF, and provides a mechanistic account at the neural level.…”
Section: Novel Theoretical Perspectivesmentioning
confidence: 99%
“…This integrated framework unites WCC and EPF, and provides a mechanistic account at the neural level. An experimental evaluation of this framework calls for time‐dependent measures, with either a strict manipulation of presentation time or an evaluation of the time course of the different processes involved .…”
Section: Novel Theoretical Perspectivesmentioning
confidence: 99%